Antidiabetic claims of Tinospora cordifolia (Willd.) Miers: critical appraisal and role in therapy - Rohit Sharma (Asian Pacific Journal of Tropical Biomedicine, 2015)
Currently, available conventional options for diabetes mellitus have certain limitations of their own, and options from medicinal plants with antihyperglycemic activities are being searched to meet the need. Antidiabetic properties of Tinospora cordifolia are highly appreciated in Ayurveda and even in recent modern researches. Several studies on its extracts (viz. immune- modulatory, anti-hyperglycemic, antioxidant, adaptogenic, hepatoprotective, hormone regulator etc.) and isolated phytoconstituents (like tinosporin, berberine, jatrorrhizine etc.) have reported that it is a preventive and curative antidiabetic herb, which are substantiated by clinical trials. Scattered information pertaining to antidiabetic potential of Tinospora is reported. Present review encompasses (i) in-depth information of reported antidiabetic activities of the plant in light of available experimental and clinical studies, and (ii) understanding on the possible mechanism of its action in combating the complex pathology of diabetes.